Strategi Pemerintah Desa dari Berbagai Tingkat Cakupan Peserta Menuju UHC di Kabupaten Karimun - Endang Lestari; Diah Ayu Puspandari (Jurnal Jaminan Kesehatan Nasional, 2023)
The government issued Presidential Instruction No. 1 of 2022 concerning Optimizing the Implementation of the JKN Program. Coverage of JKN participants in Karimun Regency is 83.28%. This study aims to explore village government strategies with various levels of participant coverage in achieving UHC in Karimun Regency. The method used in this research is a qualitative approach based on thematic analysis. Data was collected through Focus Group Discussions, in-depth interviews, and literature reviews. The research subjects were village governments with the highest, medium, and lowest UHC achievements on Karimun Island in Karimun Regency. The village government's strategy in achieving UHC included data collection and identification of individuals whom JKN does not cover; actively involving the participation of cadres of Posyandu, Posbindu and village midwives; providing education and advice; proposing JKN for poor society to the local government, and collaborating with sub-district offices and the Health Office in submitting PBIs. Implementation of this strategy is constrained by the absence of regulations regarding using village funds for JKN registration, limited funds, and JKN budgeting requires significant funds. There is a gap between the highest and lowest UHC village government strategies, including the active involvement of community cadres in the highest UHC village government. It is recommended that the most subordinate UHC village government involve the active participation of cadres from the community. The BPJS Kesehatan are advised to socialize Presidential Instruction No. 1 of 2022 to the village government